2020
DOI: 10.1038/s41391-020-0229-z
|View full text |Cite
|
Sign up to set email alerts
|

The expression of YAP1 is increased in high-grade prostatic adenocarcinoma but is reduced in neuroendocrine prostate cancer

Abstract: BACKGROUND After long-term androgen deprivation therapy, 25-30% prostate cancer (PCa) acquires an aggressive neuroendocrine (NE) phenotype. Dysregulation of YAP1, a key transcription coactivator of the Hippo pathway, has been related to cancer progression. However, its role in neuroendocrine prostate cancer (NEPC) has not been assessed. METHODS Immunohistochemistry was used to evaluate YAP1 protein levels during PCa initiation and progression. YAP1 knockdown and luciferase reporter assays were used to evaluate… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 32 publications
5
31
0
Order By: Relevance
“…However, the precise mechanism leading to PKD due to NEK1 insufficiency is not clear, but a clue came from the discovery that NEK1 interacts with and phosphorylates TAZ, involved in the E3 ligase complex, which regulates the stability of polycystin 2 [18]. TAZ is also a paralog of yes-associated protein (YAP), a transcriptional coactivator that mediates many functions in normal development and in disease pathology, such as cancer progression, including prostate cancer [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…However, the precise mechanism leading to PKD due to NEK1 insufficiency is not clear, but a clue came from the discovery that NEK1 interacts with and phosphorylates TAZ, involved in the E3 ligase complex, which regulates the stability of polycystin 2 [18]. TAZ is also a paralog of yes-associated protein (YAP), a transcriptional coactivator that mediates many functions in normal development and in disease pathology, such as cancer progression, including prostate cancer [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…However, the loss of TAZ expression has been reported in PC and it has been proposed that when TAZ is re-expressed, it results in a more aggressive disease. Contrary to this, expression in NEPC is reported as reduced or lost [80]; therefore, further investigation is still required. In breast cancers, the deubiquitinase USP1 can interact with TAZ to cause increased protein stability [104].…”
Section: Taz/wwtr1mentioning
confidence: 78%
“…They found that YAP1 is localised to basal epithelial cells in normal prostate and its protein expression increased with grade in prostate adenocarcinoma. However, upon investigation of mRNA levels in NEPCs, expression of YAP1 appears to be reduced, whilst in 12 samples that were investigated for protein expression, 6 did not show expression, with the other 6 showing staining in less than 25% of cells [80]. Therefore, it would be useful to assess not only more samples to clarify any associations of YAP expression with the NEPC phenotype, but to also investigate both the protein and the transcript in the same samples to determine whether there is a discord between the two, particularly when protein stability appears to be a key regulating factor for YAP.…”
Section: Yap1mentioning
confidence: 98%
“…In addition, these basal cells characteristically express the transcription factors SOX2 ( Figure 1F ; ref. 14 ), YAP-1 ( 15 ) and nerve growth factor receptor (NGFR, also known as p75; Figure 1D ; ref. 16 ), coupled with low-to-moderate HOXB13 expression ( Figure 1G ; ref.…”
Section: Introductionmentioning
confidence: 99%
“…In the third lineage, progenitors differentiated into luminal cell progeny, which maintained the expression of KRT8 and KRT18 while losing the expression of all other stem/progenitor markers (i.e., KRT5, KRT6A, KRT14, KRT19, and p63, Figure 1D ; GSTP1, Figure 1E ; SOX2, Figure 1F ; YAP-1 and NFGR, Figure 1D ; refs. 6 – 11 , 15 ). In addition, they acquire the expression of AR ( 6 ) and prostate-specific membrane antigen (PSMA, also known as FOLH1; ref.…”
Section: Introductionmentioning
confidence: 99%